Self managed superannuation funds and the bear market of 2007-2008 - P. J. Phillips; M. Baczynski; J. Teale (Australasian Accounting, Business and Finance Journal, 2009)
In this paper, we examine the bear market performance of self managed superannuation funds (SMSFs). Previous studies have highlighted some problems with the portfolio construction of SMSFs. This provides a rationale for examining the performance of SMSFs during the recent bear market. Based on data from two independent samples of a total of 141 self managed superannuation funds, two archetype SMSF portfolios are constructed in order to generate insights into the average performance of the funds in the samples. The performance of these funds is compared with (1) the unmanaged market index; and (2) the average returns generated by retail (balanced) superannuation funds. Interestingly, whilst the SMSFs have generated negative returns and problems with the portfolio construction remain, the relative performance of the overall portfolios vis-à-vis the market index and professionally managed funds is reasonably favourable. However, the equity portions of the SMSF portfolios suffer from under-diversification and could be more efficiently constructed.
Keywords: Self managed superannuation funds; performance; market index; retail superannuation funds